They Reached for the Moon - Oberfield, William; McCauley, Harold W. (Harold William), 1913-1977 (Salt Lake City, UT : Project Gutenberg, 2021)
"They Reached for the Moon" by William Oberfield is a science fiction story likely written in the early 1950s. This narrative explores the themes of space exploration and human consciousness as mankind attempts to achieve lunar travel, only to discover deeper truths about the mind and gravity's constraints. The book examines the psychological and philosophical implications of space flight through the experiences of the characters. The story follows two men, Pfc. Walter Jones and Pvt. Robert Moore, who are selected to embark on a pivotal mission to the Moon after previous missions have ended in silence, with no returnees. As they journey into space, initially jovial and lighthearted, their perceptions shift significantly in the low-gravity environment. They become acutely aware of their expanded mental capabilities as gravity's effects diminish. Soon, they encounter a glowing figure$1 (Ba being who explains their newfound clarity, revealing that gravity hinders intellectual and spiritual growth. Ultimately, Jones and Moore are invited to join this community of transcended beings, leaving behind their earthly origins and embarking on a deeper journey of knowledge and purpose among the stars. (This is an automatically generated summary.)s
Release date is 2021-05-12
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Space flight to the moon -- Fiction